Pengembangan Aplikasi Pemasaran Design Dekorasi Panggung Pernikahan Menggunakan Realitas Tertambah Berbasis Android - Jeremy Otniel Rorimpandey; Harya Bima Dirgantara (UNIVERSITAS KALBIS, 2022)
This study seeks to develop an application that visualizes a three-dimensional (3D) wedding stage decoration design. This research is motivated by the fact that bride and groom couples frequently lack fundamental knowledge of wedding stage decoration. Multimedia Development Life Cycle is the employed method (MDLC). This program was created with Unity 3D and uses Augmented Reality (AR) technology to manipulate three-dimensional objects. The outcome of this research is an application for Android smartphones that can convert certain markers and display three-dimensional objects of wedding decorations, allowing for greater time and energy efficiency in the selection of decorations and a more appealing marketing design. And it can be concluded from the results of the user trial that the application is feasible.